2009
DOI: 10.1136/thx.2008.103978
|View full text |Cite
|
Sign up to set email alerts
|

Associations between birth weight, early childhood weight gain and adult lung function

Abstract: Background: Low birth weight is associated with lower values for spirometry in adults but it is not known if birth weight influences other measures of pulmonary function. It is also unclear whether postnatal growth affects adult lung function. The associations between birth weight, postnatal growth and adult lung function were assessed in an unselected birth cohort of 1037 children. Methods: Birth weight, weight gain between birth and age 3 years, and lung function at age 32 years were measured. Analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
92
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 32 publications
1
92
0
2
Order By: Relevance
“…236 development of airways and alveoli occurs in early life (37). Developmental adaptations in 238 fetal life and infancy due to early life adverse exposures might result in impaired lung growth 239 with smaller airways, decreased lung volume, and subsequently to an increased risk of 240 bronchopulmonary dysplasia, asthma or COPD (9,14,38). Previous studies suggest that 241 children with asthma already have a reduced lung function in the first months of life, and that 242 this deficit progresses into childhood and early adulthood (39,40).…”
Section: Early Growth Measures and Lung Function Outcomes 176mentioning
confidence: 99%
“…236 development of airways and alveoli occurs in early life (37). Developmental adaptations in 238 fetal life and infancy due to early life adverse exposures might result in impaired lung growth 239 with smaller airways, decreased lung volume, and subsequently to an increased risk of 240 bronchopulmonary dysplasia, asthma or COPD (9,14,38). Previous studies suggest that 241 children with asthma already have a reduced lung function in the first months of life, and that 242 this deficit progresses into childhood and early adulthood (39,40).…”
Section: Early Growth Measures and Lung Function Outcomes 176mentioning
confidence: 99%
“…Likewise, Lucas et al reported that when weight gain and pulmonary function were evaluated between 5 and 14 weeks of life, higher rates of weight gain were positively associated with impaired pulmonary function (10) . Nevertheless, in the study conducted by Hancox et al, weight gain in the first three years of life was positively associated with better pulmonary capacity (functional residual capacity) in young adults (9) . The mechanisms involved in the association between fast growth and impaired pulmonary function are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in different populations have shown an effect of weight gain during infancy on pulmonary function in early (10,25) or late (9) life. A prospective study conducted in Australia concluded that fast weight gain between the first and the twelfth months of life, particularly in children of low birth weight, was associated with decreased pulmonary function at 12 months and increased symptoms of transient asthma, suggesting an important association between somatic growth and pulmonary function in childhood (25) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations